Macromia kannharaiensis, a new species of dragonfly (Insecta: Odonata: Macromiidae) from Maharashtra, India - Dalvi, Akshay; Koli, Yogesh; Thakur, Rahul (Zootaxa, 2024)
We describe a new species of dragonfly Macromia kannharaiensis sp. nov., based on a male and a female specimens collected from Dodamarg taluka, Sindhudurg district, Maharashtra. The new species belongs to the calliope–group (species group initially discussed by Laidlaw 1922), and it can be distinguished by its congeners on the bases of specific colour pattern on postclypeus, markings on S2 and S8, shape and structure of caudal appendages and accessory genitalia.